Blood lactate increases with the progression of mitral valve disease in dogs - Silva-Filho, Jorge Cardoso [UNESP]; Sousa, Marlos G.; Pereira, Evandro Zacche [UNESP]; Ortiz, Edna M. G. [UNESP]; Franco, Rodrigo P. [UNESP]; Rosa, Fernando A. [UNESP]; Camacho, Aparecido Antonio [UNESP] (Revista Pesquisa Veterinaria Brasileira, 2018)
In dogs with congestive heart failure, the upregulated sympathetic tone causes vasoconstriction that impairs peripheral blood supply, therefore causing the accumulation of lactate. In this prospective cross-sectional study with a longitudinal component, blood lactate was quantified in 10 healthy and 34 myxomatous mitral valve disease (MMVD) dogs to investigate its potential use as a diagnostic and prognostic biomarker. While there were no differences in lactate concentration between control animals and stages B1 (3.31 +/- 0.62mmol/L) and B2 (3.32 +/- 0.46mmol/L) dogs, significant differences were found between healthy (2.50 +/- 0.69mmol/L) and both C (3.99 +/- 0.47mmol/L) and D (6.97 +/- 1.23mmol/L) animals. When a cut-off of 3.35mmol/L was used, lactate was able to distinguish dogs with normal and remodeled hearts with a sensitivity of 78.2% and specificity of 63.6%. Also, significant correlations existed between lactate and indicators of cardiac remodeling. Finally, animals with blood lactate <3.5mmol/L carried a better prognosis when compared with dogs in which lactate was >5.0mmol/L. Our results suggest that the progression of MMVD results in accumulation of lactate within the bloodstream, which is likely attributable to the impaired peripheral tissue perfusion. In MMVD dogs, blood lactate may he used as a surrogate for cardiac remodeling, and an increased concentration is associated with a worse prognosis regarding the time to evolve into congestive heart failure.
Keywords: Blood lactate; mitral valve disease; dogs; hyperlactatemia; hypoperfusion; congestive heart failure; myxomatous mitral valve disease; endocardiosis